Hungary : Staff Report for the 2002 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation highlights that although economic growth of Hungary slowed in 2001, the economy showed considerable resilience to the weaker external environment. GDP growth was a still respectable 3.8 percent, down from 5.2 percent in 2000 but higher than most other countries in the region. Although export growth decelerated as the year progressed, it nevertheless outpaced growth in Hungary's export markets. Domestic demand was partly supported by buoyant private consumption on the back of strong real wage gains. Meanwhile, the unemployment rate edged down to 5.6 percent by the start of 2002.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet